2021
DOI: 10.1136/gutjnl-2020-323565
|View full text |Cite
|
Sign up to set email alerts
|

Altered faecal microbiome and metabolome in IgG4-related sclerosing cholangitis and primary sclerosing cholangitis

Abstract: ObjectiveMultiple clinical similarities exist between IgG4-related sclerosing cholangitis (IgG4-SC) and primary sclerosing cholangitis (PSC), and while gut dysbiosis has been extensively studied in PSC, the role of the gut microbiota in IgG4-SC remains unknown. Herein, we aimed to evaluate alterations of the gut microbiome and metabolome in IgG4-SC and PSC.DesignWe performed 16S rRNA gene amplicon sequencing of faecal samples from 135 subjects with IgG4-SC (n=34), PSC (n=37) and healthy controls (n=64). A subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 47 publications
1
65
0
1
Order By: Relevance
“…The faecal microbiome and metabolome have been compared between IgG4-SC and PSC. 20 Interestingly, whilst many microbial and faecal metabolic features were shared between PSC and IgG4-SC compared to HCs, IgG4-SC showed an increase in immune-related metabolites as determined by mass spectrometry. For example proinflammatory mediators such as arachidonic acid and sphinganine, the precursor of ceramide, were uniquely elevated in the faeces of patients with IgG4-SC compared to patients with PSC or HCs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The faecal microbiome and metabolome have been compared between IgG4-SC and PSC. 20 Interestingly, whilst many microbial and faecal metabolic features were shared between PSC and IgG4-SC compared to HCs, IgG4-SC showed an increase in immune-related metabolites as determined by mass spectrometry. For example proinflammatory mediators such as arachidonic acid and sphinganine, the precursor of ceramide, were uniquely elevated in the faeces of patients with IgG4-SC compared to patients with PSC or HCs.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, we used NMR metabolomics An integrated analysis of the faecal metabolome and microbiome in PSC and IgG4-SC revealed distinct disease profiles. 20 Despite a high level of microbe-metabolite correlation, faecal metabolites performed better at predicting disease status than microbial taxa. In contrast, the study presented here, is the first to apply blood-based NMR metabolomics to directly compare PSC with IgG4-SC.…”
Section: Discussionmentioning
confidence: 99%
“…From CHB to LC, Oscillibacter, Oscillospiraceae_UCG-005 , and Prevotella were depleted. The decrease of gut Oscillibacte r and Prevotella was observed in severe alcoholic hepatitis and amyotrophic lateral sclerosis (Fang et al, 2016 ; Kim et al, 2021 ), while Oscillospiraceae_UCG-005 was decrease inprimary sclerosing cholangitis (Liu et al, 2021 ). From LC to HCC, Ruminococcaceae, Clostridia_UCG-014, Oscillospiraceae_UCG-002 and Coprococcus were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in intestinal macrophages, G protein-coupled bile acid receptor 1 (GPBAR1) and Farnesoid-X-receptor (FXR) are highly expressed, which also occurs in innate immunity such as dendritic cells and natural killer cells ( 16 , 35 ). Additionally, secondary bile acids, namely, lithocholic acid and deoxycholic acid, have been reported to protect the intestinal barrier ( 38 , 39 ). Taken together, the data reported in our study indicated that alteration of bile acid homeostasis may be related to the occurrence and development of PsA.…”
Section: Discussionmentioning
confidence: 99%